What drives the unemployment rate in Maldives? An Autoregressive Distributed Lag (ARDL) approach - Ali Irushad; Mohamed Asmy Mohd Thas Thaker; Hassanudin Mohd Thas Thaker (Economic Journal of Emerging Markets, 2023)
Purpose – This paper examines factors that determine the unemployment rate in the Maldives. Methods – This paper uses an Autoregressive Distributed Lag (ARDL) model in capturing long and short-run associations among the chosen variables. It uses some macroeconomic variables, namely unemployment rate, population, economic growth, foreign direct investment, external debts, inflation rate, and expatriate workers. Findings – The empirical results suggest that except for expatriate workers, all the variables are significant determinants of unemployment rate in the long run. The study found that economic growth and inflation would negatively and significantly contribute to unemployment rate when they are combined. This explains the unemployment nexus which follows the Phillips curve and Okun’s law relationship provides the presence of both these hypotheses in the Maldives in the short-run and long-run. In addition, an increase in population and external debts worsens the unemployment situation in the Maldives. Although expatriate workers are not significant in the long run, the results reveal that they have a significant positive effect on unemployment in the short run. Implications – This result implies that the Maldivian government should encourage locals in the country to participate in the labor force and limit the participation of expatriate workers in an industry that has a shortage of skilled expertise. Originality – This study expands our understanding of key determinants of the unemployment rate in Maldives. To the best of the authors’ knowledge, this research is among the pioneer empirical study to assess the issue.